MENUMBUHKAN KEPERCAYAAN DIRI PADA ANAK USIA DINI DENGAN SENI PERAN “AKU BISA” - Annafi Nurul Ilmi Azizah; Anjar Fitrianti; Aurelia Keisha Wijaya; Karina Erna Ramadhani; Khofifah Aulia; Marfuah Amarwati; Nadya Eka Maharani; Sindi Aulia (Institut Teknologi dan Bisnis Swadharma, 2025)
The importance of character building and self-confidence from an early age serves as the foundation for implementing acting activities at TK Al Fida 3 Kartasura. This activity is presented in the form of a drama performance titled